EKSEKUSI JAMINAN BERDASARKAN UNDANG-UNDANG NOMOR 37 TAHUN 2004 TENTANG KEPAILITAN DAN PENUNDAAN KEWAJIBAN PEMBAYARAN UTANG - Fatih Fauzan Zulfa Robbi,; Rizal Rustam, (The Juris, 2022)
The background of this research is that the imposition of a postponement of debt payment obligations makes it easier for debtors to continue paying their debts and there are also legal consequences of delaying debt payment obligations. The purpose of this study is to understand the implementation of suspension of debt payment obligations and the legal consequences of confiscation status and execution of guarantees based on Law Number 37 of 2004 concerning Bankruptcy and Suspension of Payment of Debt Obligations. This study uses a normative method by analyzing problems with laws and related literature. The conclusion of this study is that the imposition of postponement of debt payment obligations only applies to concurrent creditors. The legal consequences of delaying debt payment obligations for confiscation status and execution of collateral have been regulated in Article 246 of Law Number 37 of 2004 concerning Bankruptcy and Suspension of Obligations for Debt Payment that the suspension of confiscation and execution of collateral applies during the process of delaying debt payment obligations so that the status of confiscation and execution of guarantees during the postponement of debt payment obligations to be postponed.